2016
DOI: 10.1007/978-1-4939-3816-2_30
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cognitive Function in the Water Maze Task: Maximizing Data Collection and Analysis in Animal Models of Brain Injury

Abstract: Animal models play a critical role in understanding the biomechanical, pathophysiological, and behavioral consequences of traumatic brain injury (TBI). In preclinical studies, cognitive impairment induced by TBI is often assessed using the Morris water maze (MWM). Frequently described as a hippocampally dependent spatial navigation task, the MWM is a highly integrative behavioral task that requires intact functioning in numerous brain regions and involves an interdependent set of mnemonic and non-mnemonic proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…These changes could not be ascribed to an alteration of the general motor activities secondary to the injection or the treatment since no differences were observed among the four groups of mice when the number of entries in each arm of the maze was assessed. In addition, the same treatment resulted in a significant amelioration of their spatial learning and memory as documented in the Morris water maze [30]. Thus, in the probe trial compared with WT the 3xTg mice receiving empty vector had a lower number of platform entry and time spent in the platform zone together with an increase in the latency to first entry, and all of these parameters were improved in the 3xTg mice receiving the AAV-VPS35.…”
Section: Discussionmentioning
confidence: 99%
“…These changes could not be ascribed to an alteration of the general motor activities secondary to the injection or the treatment since no differences were observed among the four groups of mice when the number of entries in each arm of the maze was assessed. In addition, the same treatment resulted in a significant amelioration of their spatial learning and memory as documented in the Morris water maze [30]. Thus, in the probe trial compared with WT the 3xTg mice receiving empty vector had a lower number of platform entry and time spent in the platform zone together with an increase in the latency to first entry, and all of these parameters were improved in the 3xTg mice receiving the AAV-VPS35.…”
Section: Discussionmentioning
confidence: 99%
“…With the knowledge that training schedule and spacing of training sessions can impact learning ability [ 10 13 , 24 , 25 ], we sought to determine if reduction of training increased the learning separation between mice affected by mTBI and controls. Our results confirmed that reduction of total number of trials increases the chance to separate learning impairment and this could be critical in a study where new compounds to reverse the injury effect are used [ 37 ] or when a smaller injury effect needs to be discovered [ 37 ]. A significant advantage using our new protocol is that more mice could be tested in one session, reducing time of testing and variability between groups.…”
Section: Discussionsupporting
confidence: 79%
“…However, due to the knowledge that training schedule and spacing of training sessions can impact learning ability [1013, 24, 25], we sought to determine if reduction of training increased the learning separation between mice affected by mTBI and controls. Our results confirmed that reduction of total number of trials increases the chance to separate learning impairment and this could be critical in a study where new compounds to reverse the injury effect are used [37] or when a smaller injury effect needs to be discovered [37]. A significant advantage using our new protocol is that more mice could be tested in one session, reducing time of testing and variability between groups.…”
Section: Discussionsupporting
confidence: 76%